The Economic Impact of Feed Efficiency in Beef Cattle - Travis D. Maddock; G. Cliff Lamb (EDIS, 2009)
AN217, a 3-page illustrated fact sheet by Travis D. Maddock and G. Cliff Lamb, describes this measure of efficiency that can be used in beef production. Includes references. Published by the UF Department of Animal Science, May 2009.